Evofosfamide sensitizes esophageal carcinomas to radiation without increasing normal tissue toxicity. (December 2019) - Spiegelberg, Linda; van Hoof, Stefan J.; Biemans, Rianne; Lieuwes, Natasja G.; Marcus, Damiënne; Niemans, Raymon; Theys, Jan; Yaromina, Ala; Lambin, Philippe; Verhaegen, Frank; Dubois, Ludwig J.
Highlights: TH-302 combined with RT enhances tumor growth delay in esophageal cancer models. This combination does not increase normal tissue toxicity on the short and long term. The increased therapeutic index (1.38) paves the way for future clinical trials. Abstract: Background and purpose: Esophageal cancer incidence is increasing and is rarely curable. Hypoxic tumor areas cause resistance to conventional therapies, making them susceptible for treatment with hypoxia-activated prodrugs (HAPs). We investigated in vivo whether the HAP evofosfamide (TH-302) could increase the therapeutic ratio by sensitizing esophageal carcinomas to radiotherapy without increasing normal tissue toxicity. Materials and methods: To assess therapeutic efficacy, growth of xenografted esophageal squamous cell (OE21) or adeno (OE19) carcinomas was monitored after treatment with TH-302 (50 mg/kg, QD5) and irradiation (sham or 10 Gy). Short- and long-term toxicity was assessed in a gut mucosa and lung fibrosis irradiation model, sensitive to acute and late radiation injury respectively. Mice were injected with TH-302 (50 mg/kg, QD5) and the abdominal area (sham, 8 or 10 Gy) or the upper part of the right lung (sham, 20 Gy) was irradiated. Damage to normal tissues was assessed 84 hours later by histology and blood plasma citrulline levels (gut) and for up to 1 year by non-invasive micro CT imaging (lung). Results: The combination treatment of TH-302 with radiotherapy resulted in significant tumor growth delay in OE19 ( P = 0.02) and OE21 ( P = 0.03) carcinomas, compared to radiotherapy only. Irradiation resulted in a dose-dependent decrease of crypt survival ( P < 0.001), mucosal surface area ( P < 0.01) and citrulline levels ( P < 0.001) in both tumor and non-tumor bearing animals. On the long-term, irradiation increased CT density in the lung, indicating fibrosis, over time. TH-302 did not influence the radiation-induced short-term and long-term toxicity, confirmed by histological evaluation. Conclusion: The combination of TH-302 and radiotherapy might be a promising approach to improve the therapeutic index for esophageal cancer patients.